A cross-sectional study on the level of knowledge,attitude and practice on diabetes mellitus among population aged 18 years old and above in Rumah Baseh, Bawang Assan, Sibu from 25th May until 7th August 2009 - Addina, binti Mohd Baki; Bong, Alan Loke Fook; Alia Maisyah, binti Ahmad Lela; Belinda Catherine, Shepherdson; Chua, Hui Heng; Deven, a/l Aragena; Hairul, bin Abdul Hamid; Komalah, a/p Subramaniam; Liang, Hui Fen; Low, Han Nee; Mohd. Azrai, bin Lahaji; Monisha Pria, a/p Samuthuan; et al. (Universiti Malaysia Sarawak (UNIMAS), 2009)
Diabetes mellitus is now recognized as an escalating non communicable disease at phenomenal scale in which WHO estimated that the nwnber of diabetics will increase to as high as 366 million people by 2030. In order to cope with the levitating prevalence of diabetes mellitus in Malaysia, level of knowledge and awareness among the population should be assessed and appropriate interventions should be employed. The purpose of this study was to identify the level of knowledge, attitude and practice concerning diabetes mellitus among the community of Rwnah Baseh, Bawang Assan, Sibu. Results obtained were then implemented to conduct an intervention beneficial to the community in order to establish effective prevention as well as promote early diagnosis and good diabetic control. Data collection was done via questionnaire based interview with the aid of set of questions constructed on basic infonnation of the respondents, their knowledge on diabetes mellitus, attitude towards the disease and practices done. The sample populations are those above 18 years of age. Data collected are analyzed with parametric & nonparametric tests. The majority of the respondents are non-diabetic. Although, their knowledge on the disease was not satisfactory as there were only 54% of respondents with good knowledge, their attitude was very good indeed with 61 %. However, total score for practice was very unsatisfactory with 72% of the respondents showed poor practice. There was significant relationship between total knowledge score and household income (p=O.013) as well as level of education (p=0.046). However, there was no significant relationship noted between total level of attitude and practice with any socio demographic factors. There was also significant positive correlation between the respondents' level of knowledge and attitude (p<0.05). In conclusion, there is great need for intervention particularly focusing on aspects o(knowledge and practice concerning diabetes mellitus in aim to ensure healthy lifestyle among the community to prevent this multi-factorial disease.